Advances in Synthetic Biology Techniques and Industrial Applications of Corynebacterium glutamicum - Yujue Wang; Qiang Wang; Aobo Sha; Kexin Ren; Mengkai Hu; Meijuan Xu; Xian Zhang; Zhiming Rao (Fermentation, 2023)
Corynebacterium glutamicum is a Gram-positive bacterium (non-spore-forming) that has been wildly used for amino acid production. Due to its stable protein secretion, low extracellular hydrolase activity, and non-toxicity, the application field of C. glutamicum has been greatly expanded. Currently, gene editing technology based on synthetic biology has great potential for synthetic biology research and genetic modification in C. glutamicum because of its ability to efficiently regulate the physiological and metabolic networks of the strain. Therefore, we summarize the gene editing tools and strategies of C. glutamicum from the aspects of genetic modification and expression elements, and we also describe the effects of gene editing techniques on a variety of products such as amino acids and their derivatives, recombinant proteins, and functional sugars, which provide a certain theoretical basis for the research on the modification of C. glutamicum strains and industrial applications. Finally, we prospect the design and industrial application of C. glutamicum genetic modification from multiple perspectives based on gene editing techniques.